1999
DOI: 10.1002/(sici)1096-8628(19990903)86:1<6::aid-ajmg2>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary agenesis, microphthalmia, and diaphragmatic defect (PMD): New syndrome or association?

Abstract: We present the prenatal diagnosis of a 22-week-gestation fetus with unilateral pulmonary agenesis, diaphragmatic hernia, microphthalmia, pulmonary vessel agenesis, and intrauterine growth retardation. The "association" of pulmonary agenesis, diaphragmatic defect, and microphthalmia was described previously in two patients but the resemblance was not noted by the authors. While each case differs slightly in some of the associated anomalies, it is evident that the mainstay of diagnosis is similar to the case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 12 publications
(12 reference statements)
0
7
0
1
Order By: Relevance
“…Ostor et al 1978 first described a premature stillborn infant with bilateral anophthalmia and pulmonary agenesis. Thereafter, there have been several other reports describing the association of pulmonary agenesis with congenital eye abnormalities [Spear et al, 1987; Engellenner et al, 1989; Berkenstadt et al, 1999]. We report on a case of a female newborn with bilateral anophthalmia and bilateral pulmonary hypoplasia with abnormal lung lobations.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Ostor et al 1978 first described a premature stillborn infant with bilateral anophthalmia and pulmonary agenesis. Thereafter, there have been several other reports describing the association of pulmonary agenesis with congenital eye abnormalities [Spear et al, 1987; Engellenner et al, 1989; Berkenstadt et al, 1999]. We report on a case of a female newborn with bilateral anophthalmia and bilateral pulmonary hypoplasia with abnormal lung lobations.…”
Section: Introductionmentioning
confidence: 73%
“…Microphthalmia and pulmonary agenesis were described in several reports and were believed to be the same spectrum of developmental anomalies as anophthalmia and pulmonary hypoplasia, respectively. Spear et al 1987 reported microphthalmia with pulmonary agenesis and Berkenstadt et al 1999 reported microphthalmia with unilateral pulmonary agenesis. Diaphragmatic herniation was also found in these two and one other report [Spear et al, 1987; Berkenstadt et al, 1999; Priolo et al, 2004] and it was thus considered by these authors to be a major feature in this pattern of anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Variable combinations of microphthalmia/anophthalmia, pulmonary agenesis/dysplasia, diaphragmatic hernia and malformative cardiac defects have been infrequently reported over the last three decades (Ostor et al, 1978;Spear et al, 1987;Smith et al, 1994;Seller et al, 1996;Berkenstadt et al, 1999;Priolo et al, 2004;Lee et al, 2006;Li and Wei, 2006;Chitayat et al, 2007;Golzio et al, 2007;Pasutto et al, 2007). Such associations have been called Matthew-Wood or Spear syndrome, while Chitayat et al (2007) devised the acronym PDAC (Pulmonary hypoplasia/agenesis, Diaphragmatic hernia/eventration, Anophthalmia/microphthalmia and Cardiac Defect), and the Mendelian Inheritance in Man database has adopted the term MCOPS9 for "syndromic microphthalmia 9" (MIM# 601186).…”
Section: Introductionmentioning
confidence: 99%
“…Microphthalmia and anophthalmia have been described with diaphragmatic defects. 10,11 CDH has also been reported with blepharophimosis, ptosis, and epicanthus inversus that were found to be associated with interstitial deletion of long arm of chromosome 3. 12 Another fetal malformation with bilateral CDH, bilateral anophthalmia, other anomalies and characteristic skin lesions has been described as a severe form of Goltz Syndrome.…”
Section: Discussionmentioning
confidence: 93%